Adherence to Antibiotic Prophylaxis in Children with Vesicoureteral Reflux - Rodriguez, Esequiel (Hindawi Publishing Corporation, 2011)
Vesicoureteral reflux (VUR) affects approximately 1% of children and may predispose a child with a bladder infection to develop pyelonephritis and renal scarring. To prevent these potential sequelae, one accepted treatment option for VUR includes low-dose continuous antibiotic prophylaxis (CAP) to maintain urine sterility until the condition resolves. Despite the widespread use of CAP, little data exists regarding adherence to long-term antibiotic therapy. Not only will poor adherence to CAP potentially preclude the intended benefit, but also nonadherence with antibiotic regimens may carry untoward effects including unnecessary treatment changes for presumed antibiotic failure, emergence of resistant organisms, and compromised clinical trial outcomes. We present an overview of medication adherence in children with VUR, discuss possible consequences of nonadherence to antibiotic prophylaxis, and suggest ways to improve adherence. We raise awareness of issues related to nonadherence relevant to healthcare providers, investigators, and the community.